HUBUNGAN PEKERJAAN IBU DENGAN MINAT KUNJUNGAN POSYANDU BALITA DI DESA NAWANGAN KABUPATEN PACITAN - Murniati Murniati; Nurhayati Nurhayati (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2018)
From data at Posyandu Nawangan Nawangan Village, Nawangan sub-district, Pacitannumber of Mother visit to Posyandu is 151 from 222 mothers. While.Bassed preface studywhich have done on November 2016, that have doing some interview with 10 persons, 7persons of them (70 percent) have professions as (4 are entrepreneur, 2 are farmer, and 1 isa civil servant), and 3 persons (30%) are housewife. From 7 persons (100%) who arelaborer all of them do not interest to visit pposyandu with the reason that they do not haveany time because they must go to work. So, a child with mother as a laborer probability willmake effect to the balita while visit posyandu. The goal of the research is to find out therelation of mother’s professions with interesting to visit Posyandu in nawangan village,nawangan subdistrict, pacitan regency.This research is kind of quantitative research approach by correlational and planning oscross sectional. Population of this research is all of the balita’s mother on February 2017 inposyandu nawangan village,nawangan subdistrict, pacitan regency on February 2017 total222 person and the sample total 83 persons with technique sampling is accidental sampling.Variable dipenden mother’s professions of balita and variable dependent the interesting tovisit posyandu. The instrument uses questionair. Statistic experiment with chi square instandart significant 0,05.Based on the result of the research has getting that balita’s mother most of 51respondent (61,4%) are laborer. Interesting to visit posyandu of mother who have balitamost of 71 respondens (85.5%) with negative interesting. There is relation between mother’sprofession with interesting to visit posyandu balita in nawangan village, nawangansubdistrict, pacitan regency, , p value = 0,031sop <a 0,05 the result reported Ho hasrejected H1 has accepted and correlation coefisient = 0,231 that means the firm level is low.The result of research has expected able to give information to balita’s mother about theimportant of posyandu balita observe grow up of balita and as a facilities to get informationand communication with local paramedis.